(untitled) (Nóema, 2016)
Those engaged in theatre encounter the “play” primarily as an aesthetic category inherent in the processes that characterise the act of the play. But with further development of these practices, the potential knowledge of the play also emerges, as human condition with a deep awareness of oneself. Through a path that passes through Breton, Plato, Huizinga, and Alessandro Fersen, an interpretation of the “play” is proposed here as a fundamental part of art and knowledge.